2018
DOI: 10.1186/s10194-018-0840-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term study of the efficacy and safety of OnabotulinumtoxinA for the prevention of chronic migraine: COMPEL study

Abstract: BackgroundOnabotulinumtoxinA is approved for the prevention of headache in those with chronic migraine (CM); however, more clinical data on the risk-benefit profile for treatment beyond one year is desirable.MethodsThe Chronic Migraine OnabotulinuMtoxinA Prolonged Efficacy open Label (COMPEL) Study (ClinicalTrials.gov, NCT01516892) is an international, multicenter, open-label long-term prospective study. Adults with CM received 155 U of onabotulinumtoxinA (31 sites in a fixed-site, fixed-dose paradigm across 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
160
3
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(205 citation statements)
references
References 29 publications
18
160
3
5
Order By: Relevance
“…In adults, it has been established in the pooled PREEMPT studies that a meaningful proportion of patients who failed to respond to the first treatment became responders after additional treatment cycles . In addition, the results of the long‐term, open‐label COMPEL study showed that the mean reduction in the number of headache days per 28 days was greater after 9 treatment cycles (108 weeks; −10.7 headaches) than after 2 treatment cycles (24 weeks; −7.4 headaches) . Therefore, a longer study to explore the safety and efficacy of repeated exposure to onabotulinumtoxinA in the developing adolescent, with at least 2 treatment cycles, may be necessary in this population to detect significant differences between onabotulinumtoxinA and placebo treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In adults, it has been established in the pooled PREEMPT studies that a meaningful proportion of patients who failed to respond to the first treatment became responders after additional treatment cycles . In addition, the results of the long‐term, open‐label COMPEL study showed that the mean reduction in the number of headache days per 28 days was greater after 9 treatment cycles (108 weeks; −10.7 headaches) than after 2 treatment cycles (24 weeks; −7.4 headaches) . Therefore, a longer study to explore the safety and efficacy of repeated exposure to onabotulinumtoxinA in the developing adolescent, with at least 2 treatment cycles, may be necessary in this population to detect significant differences between onabotulinumtoxinA and placebo treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The findings also offer insights on study design that can be used to guide future research into the efficacy of onabotulinumtoxinA for the prevention of migraine in adolescents with CM. In adults, the beneficial effects of onabotulinumtoxinA have been shown to increase with multiple treatments . Therefore, to fully assess the benefits of treatment in adolescents, we suggest that future pediatric trials evaluate at least 2 treatment cycles of onabotulinumtoxinA, enroll larger numbers of patients, and explore the use of a placebo run‐in or crossover design.…”
Section: Discussionmentioning
confidence: 99%
“…Since PREEMPT regulatory trials were done, several open‐label and real‐life pragmatic studies have already demonstrated the effectiveness of onabotulinumtoxinA in terms of frequency and analgesic intake as main end‐points but also in improving headache intensity and quality of life .…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Its mechanism of action may include blocking the release of inflammatory neuropeptides from stimulated sensory neurons including substance P and calcitonin gene-related peptide (CGRP) 13 and may decrease the promotion of central sensitization. 15,16 Patients with chronic migraine who do not respond to the first treatment cycle of onabotA are recommended to try at least 2 or 3 treatments before the determination of efficacy. 15,16 Patients with chronic migraine who do not respond to the first treatment cycle of onabotA are recommended to try at least 2 or 3 treatments before the determination of efficacy.…”
Section: Introductionmentioning
confidence: 99%